Tolerance in Minahasan Local Knowledge - Winoto, Darmawan Edi; Dasfordate, Aksilas; Pelealu, Aldegonda Evangeline; Imbar, Meike (Universitas Negeri Semarang, 2024)
Discrimination can manifest in numerous ways. At its core, intolerance can have devastating consequences, including dehumanizing people and making them feel insignificant or inferior, leading to social exclusion and violence. Discrimination has the potential to have a devastating impact on mental health, especially in immigrant communities. Analyzing written transcripts, field notes, and recorded conversations yields themes and insights from qualitative research. Interviews are used by data collection techniques to collect information from participants regarding their experiences or opinions on specific topics. Some members were dissatisfied with its independence from Dutch-established churches, while others desired to incorporate traditional beliefs. These debates remain central to the development of Christian identity in Minahasa today. Although religion and tradition are frequently intertwined, many villagers believe that preserving their religious heritage is essential to preserving their sense of identity; however, this has proven more difficult as Protestant churches have been less accommodating of cultural practices in their services.